2023
DOI: 10.1039/d2tc05014e
|View full text |Cite
|
Sign up to set email alerts
|

Phase behaviour of liquid crystalline dendronized fullerene binary mixtures

Abstract: Here we describe liquid crystalline binary mixtures of [60]fullerene with wedge-shaped tris-(alkyl)gallate group attached via flexible spacer, where alkyls are n carbons long (C60-n). Phase behaviour was investigated as a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Previously, we have reported a series of [60]fullerene block molecules, C m −C 8 −C 60 (m=5–8, referred to as 5 – 8 , 6 – 8 , 7 – 8 , and 8 – 8 in this paper), where [60]fullerene is connected with alkyl tails substituted gallic ester via an octamethylene flexible spacer (Figure 1a). [41–45] It has been found that they can form lamellar LCs based on self‐assembled fullerene two‐dimensional (2D) crystals, among which there are triple (L T , low temperature phase of block molecules 5 – 8 , 6 – 8 , and 8 – 8 ) or quadruple (L Q , high temperature phase of block molecules 5 – 8 , 6 – 8 , 7 – 8 , and 8 – 8 ) layers of C 60 sandwiched by hydrocarbon tails (Figure 1b–c). [38,41–43] Besides, a novel superlattice lamellar LC phase ( SL67 ${{{\rm S}{\rm L}}_{6}^{7}}$ ) with multiple sublayer was reported for block molecule 7 – 8 at low temperatures [44] .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have reported a series of [60]fullerene block molecules, C m −C 8 −C 60 (m=5–8, referred to as 5 – 8 , 6 – 8 , 7 – 8 , and 8 – 8 in this paper), where [60]fullerene is connected with alkyl tails substituted gallic ester via an octamethylene flexible spacer (Figure 1a). [41–45] It has been found that they can form lamellar LCs based on self‐assembled fullerene two‐dimensional (2D) crystals, among which there are triple (L T , low temperature phase of block molecules 5 – 8 , 6 – 8 , and 8 – 8 ) or quadruple (L Q , high temperature phase of block molecules 5 – 8 , 6 – 8 , 7 – 8 , and 8 – 8 ) layers of C 60 sandwiched by hydrocarbon tails (Figure 1b–c). [38,41–43] Besides, a novel superlattice lamellar LC phase ( SL67 ${{{\rm S}{\rm L}}_{6}^{7}}$ ) with multiple sublayer was reported for block molecule 7 – 8 at low temperatures [44] .…”
Section: Introductionmentioning
confidence: 99%